Numerical simulation of water-bearing coal goaf using ground-borehole TEM—a case study of Tongxin Coal Mine, Shanxi Provice, China - Yang, Yang; Peng, Sanxi; Shan, Huimei; Peng, Qinghua (Frontiers in Earth Science, 2024)
Transient electromagnetic method (TEM) is widely used in coalfield hydrogeological exploration and goaf investigation. However, given the limitations of the method, the vertical resolution of ground TEM is somewhat low for effectively detecting water-bearing coal goaf.Compared with ground TEM, ground-borehole TEM is characterized by a relatively better ability for detecting low-resistivity target bodies. In this study, a low-resistivity thin plate model was established, and the ground-borehole TEM electromagnetic responses of different points (within and without of the plate) were numerically simulated. We considered an exploration project in Datong City (Shanxi Province, China) as a study case, to conduct the field investigation, examine the characteristics of ground-borehole TEM electromagnetic responses under different situations, and validate the numerical model as well, including (a) water-bearing coal goaf and (b) solid coal. The result showed that, (a) the longer the sampling time is, the weaker the electromagnetic response of ground-borehole TEM will be;(2) ground-borehole TEM stands out with a high vertical resolution for water-bearing coal goaf; (c) the extreme points of the Z component and the polarity changing points of the X and Y components can indicate the interface where the physical properties alternated.